2019
DOI: 10.3390/w11020396
|View full text |Cite
|
Sign up to set email alerts
|

Iron Isotopic Composition of Suspended Particulate Matter in Hongfeng Lake

Abstract: The geochemical study of iron isotopes is of great significance to deeply understand the surface material circulation process and its environmental effects in surface and subsurface environments. Eutrophication lakes are an important part of the surface and subsurface environment; however, knowledge of the geochemical behavior and fractionation mechanism of iron isotopes in the biogeochemical cycling of eutrophication lakes is still scarce. In this study, a eutrophic lake with seasonal anaerobic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Nasiri et al build expert system to calculate the water pollution index [22]. Zheng et al use chemistry to study the causes of eutrophication in Hongfeng Lake [23]. Among them, game theory, which is used to analyze human social conflicts and cooperation, provides a good analytical tool for river pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Nasiri et al build expert system to calculate the water pollution index [22]. Zheng et al use chemistry to study the causes of eutrophication in Hongfeng Lake [23]. Among them, game theory, which is used to analyze human social conflicts and cooperation, provides a good analytical tool for river pollution.…”
Section: Introductionmentioning
confidence: 99%
“…SPM concentration in water was also an important factor affecting the partition coefficient of heavy metals in SPM [86]. Studies on rivers in the Yangtze River system showed that the δ 56 Fe value in the SPM of the rivers and lakes in southern China varied between −1.36 and 0.07‰, with a highly linear relationship between δ 56 Fe and Fe/Al, which proved that the terrestrial source SPM carried by the main tributaries of lakes had an essential effect on Fe in the lakes [39]. Cd, As, Pb, and Se in the Yangtze River were highly enriched in SPM, and SPM concentration and water pH controlled the adsorption of metals by particles [40].…”
Section: The Sorption Of Heavy Metals On Spmmentioning
confidence: 94%